Playful strategies for entrepreneurial minds: an analysis of gamification in education - Espinoza Casco, Roque Juan (2024)
The study aimed primarily to analyze the connection between gamification and the promotion of entrepreneurship among students in a university. To address this issue, a non-experimental, cross-sectional, correlational, and causal methodology was employed, with a predominantly quantitative approach. The study population comprised 120 third-grade students from a specific school, from which a sample of 43 students from the "A" class of the third grade was selected. The data collection technique used was a survey, facilitated through a questionnaire designed for this purpose. The attained results unveiled that the variable "Gamification" indicated a "Moderate" level, while the variable "Entrepreneurship" demonstrated a "Moderate" level as well, with a total of 5 participants falling into this particular category. Totals for each level of "Entrepreneurship" and "Gamification" were synthesized, along with the overall total of participants in the study, amounting to a total of 43 participants. In terms of educational implications, the study concluded that gamification correlates with entrepreneurship, fostering the develop-ment of skills for the youth's future endeavors.